The Values of Moral Education in View Imam Al-Ghazali (Analysis Study of The Book Ihya'ulumuddin) - Qurba, Al-Qanit; Auliana, Primaresa; Ahmad, Aprizal; Said, Mukti (Jurnal Prajaiswara, 2025)
Introduction: This study arises from the observable moral decline in society, visible both directly and through various media, which underscores the urgency of re-examining moral education. The research is limited to four main issues: (1) the importance of akhlak mahmudah and the dangers of akhlak mazmumah, (2) the nature of virtuous and vicious morals, (3) ways to cultivate good character, and (4) the starting point of moral education. The objectives are to understand the importance and risks of moral qualities, to clarify the essence of good and bad morals, to identify methods for nurturing virtuous character, and to outline the path towards moral education. Research Methods: This research uses a library research method, drawing primarily on volume II of Imam al-Ghazali’s Ihya’ ‘Ulum al-Din, translated by Prof. T.K.H. Ismail Yakub, which elaborates the basic principles of religion with a focus on ethics, soul training, refinement of character, and treatment of spiritual diseases. Secondary data are taken from other works on moral education. The data are analyzed using both deductive and inductive approaches. Finding/Results: The findings show that Imam al-Ghazali grounds moral education in four principal virtues: wisdom, courage (shaja’ah), self-restraint or self-respect (iffah), and justice. Wisdom enables a person to distinguish truth from falsehood and right from wrong. Courage is the power of anger governed by reason. Self-restraint directs desire under the guidance of intellect and religion so that noble traits emerge. Justice regulates and harmonizes anger and desire under reason and religious guidance, thereby producing balanced and just character.